Estimation of Material Requirements and Coating Costs in Fiberglass Pilot Boat Hull Reparation - Nizam Masbakhi Zain; Soffiana Agustin; Fahmy Ardhiansyah (Universitas Muhammadiyah Gresik, 2022)
Abstract The purpose of painting the ship is to improve the quality of the ship's hull. Superior painting techniques and materials result in a hull that is resistant to seawater and air corrosion, the painting process and procedures related to painting, since almost all of the ship's building materials are metallic finishes. In order for the paint to meet the specified requirements, it must comply with the specified painting process, one of which is the painting process according to Utomo (2019) pre-inspection, surface preparation, paint preparation, and paint application. For that, you need to know the various types of painting techniques that must be prepared before carrying out the hull painting process. Metal is very sensitive to corrosion, because the working area of the ship is near the sea. Repairs to ships are important things that need to be done routinely and need regular planning to ensure that at any time they can sail and operate safely. one of the maintenance of the ship is painting the purpose of painting is to improve the quality of the hull. One good technique with several stages, namely pre-inspection, surface preparation, paint preparation, and paint application can produce a hull that is resistant to damage from seawater and air. the repair process that is needed is coating. To find material requirements and coating costs, use a comparison of 2 local A paint products and international B paint products. Then it can be seen that the total coating requirement for the most economical 12 meter pilot boat is Cat B with a total of 453.15 liters and a cost of 36,692,619. Keywords: Coating, and Material Requirements